Melting ice. (21st November 2017) - Benedetto, Elmo
Abstract: In this brief frontline, we want to describe the well-known fact that, when freshwater ice melts, the freshwater liquid level does not change. In the Italian Ministerial programs, fluid statics is introduced in the three years of middle school (students of 11–13 years) and during the first two years of high school (14–15 years). The Italian textbooks do not clearly explain why the abovementioned phenomenon occurs. The explanations are qualitative and they may lead to misinterpretation. I have noted that the students are very curious about this phenomenon. They sought a demonstration from books and from the web; and when they do not find it they asked me. Moreover, they have allowed me to observe that there are contradictory statements about the melting of icebergs. Some authors claim that they would not raise the sea-level, others say the opposite. Honestly speaking, I had never thought about this phenomenon and in classroom I tried to give them proof, expressing my opinion about the melting of icebergs.